Accounting Conservatism, the Quality of Earnings, and Stock Returns - Penman, Stephen H.; Zhang, Xiao-Jun (The Accounting Review, 2002)
When a firm practices conservative accounting, changes in the amount of its investments can affect the quality of its earnings. Growth in investment reduces reported earnings and creates reserves. Reducing investment releases those reserves, increasing earnings. If the change in investment is temporary, then current earnings is temporarily depressed or inflated, and thus is not a good indicator of future earnings. This study develops diagnostic measures of this joint effect of investment and conservative accounting. We find that these measures forecast differences in future return on net operating assets relative to current return on net operating assets. Moreover, these measures also forecast stock returns—indicating that investors do not appreciate how conservatism and changes in investment combine to raise questions about the quality of reported earnings.